Research on the history of Polish intelligentsia during the partition period - Molik, Witold (Galicja. Studia i materiały, 2024)
The presented text is an attempt to characterize research on the history of the Polish intelligentsia during the period of partitions, conducted since the 1960s within two directions treating the intelligentsia as a socio-professional stratum and as an opinion-forming stratum, exerting a multifaceted influence on the Polish society. This article does not claim to exhaust the extensive topic in either methodological or practical research postulates. First of all, it expresses the author’s position and is an invitation to discuss the future of research, also in the field of social history, on the history of the Polish intelligentsia during the period of partitions, especially in Galicia.